Juliet Mitchell and the Lateral Axis
VI, 291 p.
Keywords: This volume fills the gap in books dedicated to the ideas of ground-breaking theorist Juliet Mitchell. Essays from internationally renowned scholars address themes that cross-cut her oeuvre: equality, violence, collective movements, subjectivity, sexuality and power. Mitchell herself contributes a chapter and an afterward.